Cooperative NOMA-Enabled SWIPT IoT Networks With Imperfect SIC: Performance Analysis and Deep Learning Evaluation - Vu, Thai-Hoc; Nguyen, Toan-Van; Kim, Sunghwan (IEEE internet of things journal, 2022)
In this article, we propose a cooperative nonorthogonal multiple access (NOMA)-enabled simultaneous wireless information and power transfer (SWIPT) Internet of Things (IoT) networks, where one information source harvests energy from a multiantennas power beacon (PB) to serve two IoT users via the help of multiple energy-limited relay nodes. To improve the performance of far IoT user, we propose reactive and proactive relay selection protocols together with time-power energy harvesting mechanism under imperfect successive interference cancellation. Closed-form expressions for the outage probability (OP), throughput, and energy efficiency (EE) of the proposed system are obtained, from which the asymptotic analysis for the throughput is also carried out. To further enhance the system performance, we propose a low-complexity method to optimize the outage and throughput performance subject to power allocation, time, and power splitting parameters. Toward real-time configurations in IoT networks, we design a deep learning framework for the sum-throughput and EE predictions with low computation complexity and high accuracy. The influences of antennas setting at PB, time-switching ratio, power-splitting ratio, power allocation factor, and the number of relays on the system OP, throughput, and EE are evaluated and discussed along with numerical results.